Nonlinear Deformable-body Dynamics - Luo, Albert C. J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Nonlinear Deformable-body Dynamics" mainly consists in a mathematical treatise of approximate theories for thin deformable bodies, including cables, beams, rods, webs, membranes, plates, and shells. The intent of the book is to stimulate more research in the area of nonlinear deformable-body dynamics not only because of the unsolved theoretical puzzles it presents but also because of its wide spectrum of applications. For instance, the theories for soft webs and rod-reinforced soft structures can be applied to biomechanics for DNA and living tissues, and the nonlinear theory of deformable bodies, based on the Kirchhoff assumptions, is a special case discussed. This book can serve as a reference work for researchers and a textbook for senior and postgraduate students in physics, mathematics, engineering and biophysics. Dr. Albert C.J. Luo is a Professor of Mechanical Engineering at Southern Illinois University, Edwardsville, IL, USA. Professor Luo is an internationally recognized scientist in the field of nonlinear dynamics in dynamical systems and deformable solids.
Tensor Analysis -- Deformation, Kinematics and Dynamics -- Constitutive Laws and Damage Theory -- Nonlinear Cables -- Nonlinear Plates and Waves -- Nonlinear Webs, Membranes and Shells -- Nonlinear Beams and Rods.
Keywords: Physics; Differentiable dynamical systems; Materials; Physics; Classical Continuum Physics; Dynamical Systems and Ergodic Theory; Continuum Mechanics and Mechanics of Materials; Statistical Physics, Dynamical Systems and Complexity